Breastfeeding and child development - Pollitt, Ernesto (1998)
This brief review focuses on the advantages and disadvantages of human lactation for the mental development of children. The review covers theree tapies: (1) Correlation between type of feeding and  performance  on  different  mental  tests  administered befare and after the first three years of postnatal life, (2) Prevention of nutritional deficiencies that have adverse effects on cognition and prevention of sequels from pre-term births and low birth weight; (3) Contamination of human milk.The purpose is to provide a representative view of these three tapies. Our evaluation of the publised data shows that the information does not allow for definitive conclusions, particularly in reference to the first and third tapie. The  strongest available evidences is found on studies of the effects of free fatty acids on cerebral growth and on longitudinal studies of pre-term children of low birth weight. In our impression it is necessary to evaluate carefully the recommendation of the World Health Organization regarding the benefits of lactation in those cases when drugs or enviromental minerals and chemicals  have contaminated human milk.